2012
DOI: 10.1007/s10957-012-0219-y
|View full text |Cite
|
Sign up to set email alerts
|

Facial Reduction Algorithms for Conic Optimization Problems

Abstract: To obtain a primal-dual pair of conic programming problems having zero duality gap, two methods have been proposed: the facial reduction algorithm due to Borwein and Wolkowicz [1,2] and the conic expansion method due to Luo, Sturm, and Zhang [5]. We establish a clear relationship between them. Our results show that although the two methods can be regarded as dual to each other, the facial reduction algorithm can produce a finer sequence of faces including the feasible region. We illustrate the facial reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(135 citation statements)
references
References 20 publications
2
133
0
Order By: Relevance
“…Waki and Muramatsu [26] considered a FRA for conic programming and showed that FRA can be regarded as a dual version of CEA. See the excellent article by Pataki [15] for an elementary exposition of FRA, where he points out the relation between facial reduction and extended duals.…”
Section: Given a Weakly Infeasible Sdfp How Can We Generate A Weaklymentioning
confidence: 99%
See 3 more Smart Citations
“…Waki and Muramatsu [26] considered a FRA for conic programming and showed that FRA can be regarded as a dual version of CEA. See the excellent article by Pataki [15] for an elementary exposition of FRA, where he points out the relation between facial reduction and extended duals.…”
Section: Given a Weakly Infeasible Sdfp How Can We Generate A Weaklymentioning
confidence: 99%
“…We now take a closer look at the connection between FRA/CEA and FP. More details on FRA can be found in [15] and [26]. In [26], it is also explained the connection between FRA and CEA, see section 4 therein.…”
Section: Is Then Updated and It Becomes {(mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there has been a significant renewed interest in facial reduction, in large part due to the success in applications for graph related problems, such as Euclidean distance matrix completion and molecular conformation [76,75,46,6] and in polynomial optimization [110,111,74,141,140]. In particular, a more modern explanation of the facial reduction procedure can be found in [88,104,107,136,142].…”
Section: Related Workmentioning
confidence: 99%